The relationship between the anxiety level of breastfeeding mothers and the amount of milk production in Mothers who have babies aged 1-12 Months in Sigumpar Dangsina Village, Sigumpar Health Center Working Area - Melva Epy Mardiana Manurung; Lidia Silaban; Veronica Silalahi (International Journal of Health Engineering and Technology, 2022)
Breast milk is a liquid that contains white blood cells, immune substances, enzymes, hormones, and proteins that are suitable for babies. Breast milk is an ideal source of nutrition, rich in food essences that can accelerate the growth of brain cells and the development of the nervous system. In breastfeeding, mothers often experience anxiety caused by milk production. Breast milk production can be influenced by several factors, namely infant birth weight, gestational age, maternal age and parity, maternal stress/illness, smoking, alcohol consumption, consumption of contraceptive pills, maternal diet, husband and family support, breast care, type of delivery and hospitalization. when giving birth. Mothers who experience anxiety will cause the let-down reflex to occur, resulting in disruption of breast milk production due to inhibition of the production of the hormones prolactin and oxytocin. This study aims to The relationship between the anxiety level of breastfeeding mothers and the amount of milk production in Mothers who have babies aged 1-12 months in Sigumpar Dangsina Village, Sigumpar Health Center Working Area. This research is a quantitative research with cross sectional data collection approach. The population of this study were all breastfeeding mothers who had babies 1-12 months. The sampling technique used is a total sampling of 17 respondents. The data was processed by Spearman correlation test. The results showed p value = 0.003 so p < 0.05 which means that there is a relationship between the level of anxiety of mothers who breastfeed their babies to the amount of milk production in mothers who have babies aged 1-12 months in Sigumpar Dangsina Village, Sigumpar Health Center Work Area. Mothers/Communities and their families support each other in breastfeeding so as not to cause anxiety in breastfeeding mothers